The once and future worker : a vision for the renewal of work in America - Cass, Oren, 1983- (Encounter Books, 2018)
With Donald Trump's rise to the presidency has come widespread awareness of the economic and social crisis facing much of the nation. Yet while everyone now cares, no one understands what happened or knows what to do. Most recommendations presume that we should proceed down our present path while somehow creating better government programs to drag along everyone falling behind. "I'm for globalization and a strong safety net" seems likely to become for the next generation of insulated but determinedly respectable professionals what "I'm socially liberal and fiscally conservative" was for the last. How this differs from what we have been trying, or why it should work better, is anyone's guess. The Once and Future Worker steps into this gaping void. It explains how decades of bad public policy, not irresistible and uncontrollable forces, have pushed America to the brink. The 1960s are known for their social upheaval, but the decade also marked the bipartisan transition to a national economic policy that sacrificed the needs and interests of workers in pursuit of faster growth and rising consumption. That mistake has eroded the foundation of productive work and destabilized the structures of family and community on which long-term prosperity depends. Looking through the lens of work flips the national debate on its head-or, rather, returns it to its feet. New approaches to reform emerge for the environment and organized labor, trade and immigration, education and the safety net. "Growing the economic pie" transforms from a pleasant platitude to the most insidious phrase in politics. The result is dismay at what we have done to ourselves, but also optimism that a thriving society remains within reach.